Borderline Lepromatous Leprosy with Mild Reversal Reaction in Child - Fonna, Nellia; Ariani, Tutty; Rizal, Yosse; Yenny, Satya Wydya (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: Childhood leprosy is an important marker of the status of the ongoing leprosy control program, as it is an indicator of active disease transmission in the community. Children are believed to be the most vulnerable group to infection with M. leprae due to their immature or nascent immunity and exposure to intrafamilial contacts. Case report: A 8 years ole male patient presented with hypopigmented patch and erythematous patch with not itchy, not pain, and loss of sensation which increasing more since 1 week ago. Initially 2 months ago, white patch that felt numbness appeared on the back, then white patches wider and spread to the chest, both arms and thighs. Dermatologic finding showed erythematous plaques, hypopigmentation macule with infiltration on cheek, back, both of arms, xerosis cutis. Decreased sensory function was found in the median, ulnar and posteriol tibial nerves. Acid-fast bacilli (AFB) staining revealed bacterial index (BI) +5 and morphological index (MI) 80%. Histopathological examination showed atrophic stratified squamous epithelium, grenz zone, many groups of foamy macrophages reached the fat layer. The patient was diagnosed Morbus Hansen borderline lepromatous leprosy type with mild reversal reaction and treated with MDT-MB drug package, vitamin B complex tablet, zinc tablet, paracetamol tablet, and 10% urea cream on dry skin 2 times a day on dry skin after bath during 2 month and the lesion was reduced. Conclusion: The rate of childhood leprosy continues to be a significant problem. There is a clear need to strengthen early detection, treatment, and regular follow up of these cases in both high and low endemic setting is essential in the prevention of deformities.